An Evaluating Facility Management Maintenance Strategies of Laboratory Building at UTHM, Pagoh in Comparison with the ISO 41001:2018 Standard - Roslizuri, Nur Intan Balqis; Mohd Fahmi Abdul Rahman (Progress in Engineering Application and Technology, 2026)
This study evaluates the facility management (FM) maintenance practices strategies of laboratory building at Universiti Tun Hussein Onn Malaysia (UTHM), Pagoh Campus. The research aims to identify the effectiveness, consistency, and adequacy of current maintenance management, evaluate the building’s operational performance in terms of functionality, responsiveness, safety, and sustainability, and propose strategies for improvement. The study was conducted using a quantitative approach through structured questionnaires distributed to UTHM students, laboratory technicians and Sime Darby Property Facility Management staff. A total of 52 respondents participated, representing key personnel directly involved in maintenance and facility operations. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) to obtain demographic analysis, descriptive statistics, including means, frequencies, and standard deviations, and to test reliability using Cronbach’s Alpha. The findings revealed that while existing maintenance practices are functional, challenges remain in preventive maintenance scheduling, communication, and the integration of technology-based facility management systems. The study concludes that adopting data-driven and preventive maintenance strategies can significantly improve efficiency, sustainability, and user satisfaction. The findings provide valuable insights for UTHM facility managers and contribute to the broader discourse on improving FM practices in higher education laboratory environments.